2009
DOI: 10.1103/physrevb.79.045207
|View full text |Cite
|
Sign up to set email alerts
|

Defects in AlSb: A density functional study

Abstract: We carry out density functional calculations to study both intrinsic and extrinsic defects in AlSb. We focus on the carrier compensation and trapping properties of these defects, which are important to the radiation detection applications. We show that the Sb antisite ͑Sb Al ͒ is a low-energy defect, with interesting property of light-induced metastability, similar to the As antisite in GaAs. Sb Al is effective in compensating holes induced by the residual carbon but is also a deep electron trap that reduces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Similar results were also found for Sb Al antisite in AlSb in Ref. 12, were charge states from + 2 to −1 were found to be stable. We also performed LDA calculations for the Sb Ga antisite, with the same system settings (system size and energy correction term) as with the HSE06 functional.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results were also found for Sb Al antisite in AlSb in Ref. 12, were charge states from + 2 to −1 were found to be stable. We also performed LDA calculations for the Sb Ga antisite, with the same system settings (system size and energy correction term) as with the HSE06 functional.…”
Section: Resultssupporting
confidence: 76%
“…10 and 11) but very interestingly also in AlSb (Ref. 12). The prediction of the Sb Ga donor levels associated with low defect formation energies is a challenge for explaining the Even though our main focus is on the native point defects, we also perform a very limited study of extrinsic point defects, namely carbon at the substitutional Sb site and oxygen at the interstitial cation site as possible sources of p-type conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Its ground state has T d symmetry, and Du has discovered a metastable configuration with C 3V symmetry. 10 The formation energies of Sb Al ͑T d ͒ and Sb Al ͑C 3V ͒ obtained using the HSE06 hybrid functional are shown in Fig. 7.…”
Section: Survey Of Defects In Alsbmentioning
confidence: 99%
“…Previous DFT calculations [8][9][10] have shown that at the lower part of the band gap, the intrinsic defects that have low formation energies are the aluminum interstitial ͑Al i ͒ and the antimony antisite ͑Sb Al ͒. We first look at Al i .…”
Section: Survey Of Defects In Alsbmentioning
confidence: 99%
See 1 more Smart Citation